2010
DOI: 10.1002/srin.201000038
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Simulation of Thermosolutal Convection and Macrosegregation in Steel Ingots

Abstract: Thermosolutal convection and macrosegregation formation during the solidification of steel ingots are numerically simulated in three dimensions. The simulation is based on a fully coupled model for mass, momentum, energy, and species conservation equations. The interdendritic flow in the mushy zone is governed by Darcy's law, and the permeability term is discretized using an interpolated liquid fraction method. The numerical results for a benchmark test of macrosegregation in a Pb‐Sn alloy are compared with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…[21]. Generally, the numerical results of the present model are in good agreement with the measurements by Hebditch and Hunt [22].…”
Section: Macrosegregation With Multiple Pouring and Validationsupporting
confidence: 89%
“…[21]. Generally, the numerical results of the present model are in good agreement with the measurements by Hebditch and Hunt [22].…”
Section: Macrosegregation With Multiple Pouring and Validationsupporting
confidence: 89%
“…Li et al (2013) and Wu and Ludwig (2006) suggested that the negative segregation is caused by the sedimentation of grains when grains solidified from liquid phase. However, Li et al (2010) found that the solutal buoyancy is also an important factor for the formation of both the top positive segregation and the lower conic negative segregation. In current model, both sedimentation of grains and solutal buoyancy are treated as key factors for the formation of above segregations.…”
Section: Characteristics Of Segregationmentioning
confidence: 95%
“…14. The total solidification time for this 3?3 t Fe-3?6 wt-%C steel ingot is y105 min, as calculated by Li and Shen, 28 whereas in the present model it is y90 min under the same solution conditions. However, different solid fractions are presented as show in Fig.…”
Section: Initial Conditions and Boundary Conditionsmentioning
confidence: 99%